Analisis Pengaruh Indeks Pembangunan Manusia, PDRB Per Kapita dan Jumlah Penduduk terhadap Jumlah Penduduk Miskin di Kalimantan Selatan Tahun 2010-2017 - Anggraini, Faradina; Rusdiansyah (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Poverty is one of an obstacle faced by nearly all countries around the world,mainly for developing countries. Poverty may be caused by many things such as a lowlevel of education, low level of health, limitation of access towards goods andservices, high level of unemployment, the high and rapid growth of population, lowlevel of income, and others.This study aims to analyze the impact of the Human Development Index, GrossDomestic Regional Product per capita, and Population of Poor People in SouthKalimantan. The method of analysis used in this research is Ordinary Least Square(OLS). Using panel data (pooled data), the combination of time series data startedfrom 2010 until 2017 and cross-section data of 13 regencies/cities in SouthKalimantan. The analysis in this research doing with the help of Eviews 9 software.This research shows that Human Development Index and Population have apositive effect and not significant on the low population in South Kalimantan.Meanwhile, Gross Domestic Regional Product has a negative impact and meaningfulon the bass population in South Kalimantan. Those three variables have a significanteffect simultaneously on low people in South Kalimantan.